2003
DOI: 10.1002/joc.935
|View full text |Cite
|
Sign up to set email alerts
|

Urbanization and seasonal temperature trends: observational evidence from a data‐sparse part of North America

Abstract: Viewed from the continental or hemispheric perspective, the evidence of warming trends in surface temperatures continues to accumulate. Here, we focus on the detection of seasonal temperature trends at regional and sub-regional space scales. The study region is transnational, extending from the border areas of New Mexico and Texas in the USA, southward into the altiplano of north central Mexico. The analysis considers maximum and minimum temperature records from 21 stations located in a variety of land-use en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 28 publications
2
22
0
1
Order By: Relevance
“…This result is based on a large number of data series (more than 1200) and recently confirmed by Englehart and Douglas (2003). The most consistent results were found with a coefficient a = (2.39 ± 0.70)·10 −3 K (±95%) for minimum temperatures (Karl et al, 1988).…”
Section: The Empirical Urban Adjustmentsupporting
confidence: 79%
“…This result is based on a large number of data series (more than 1200) and recently confirmed by Englehart and Douglas (2003). The most consistent results were found with a coefficient a = (2.39 ± 0.70)·10 −3 K (±95%) for minimum temperatures (Karl et al, 1988).…”
Section: The Empirical Urban Adjustmentsupporting
confidence: 79%
“…In developing the data set, we attached substantial weight to the concept that the impact of urban warming on SAT records is generally proportional to population (e.g. Karl et al, 1988;Englehart and Douglas, 2003). Consequently, the decision was made to include only stations that are located in .…”
Section: Data Set Developmentmentioning
confidence: 99%
“…Recently, this line of inquiry has been extended to include much of northern * Correspondence to: Phil J. Englehart,3500 N 57th St.,Kansas City,KS 66104,USA; Mexico and the border region of the USA (Englehart and Douglas, 2003). Several factors may explain why SAT variability for Mexico has not received more research attention.…”
Section: Introductionmentioning
confidence: 99%
“…where no buildings existed previously, was monitored by Landsberg and Maisel (1972), who reported that over a period of 3 years, a heat island of up to 4.5°C appeared as the newly established town of Columbia, Maryland grew to a population of 10 000 residents. Analyses of longterm temperature records in several locations -Turkey (Tayanc and Toros, 1997); Alaska (Magee et al, 1999); Athens (Philandras et al, 1999); South Korea (Choi et al, 2003); and North America (Engelhart and Douglas, 2003) -show an increase in the UHI effect paralleling increasing urbanisation.…”
Section: Introductionmentioning
confidence: 99%